2023
DOI: 10.1126/scirobotics.adg3679
|View full text |Cite
|
Sign up to set email alerts
|

Neuromorphic sequence learning with an event camera on routes through vegetation

Le Zhu,
Michael Mangan,
Barbara Webb

Abstract: For many robotics applications, it is desirable to have relatively low-power and efficient onboard solutions. We took inspiration from insects, such as ants, that are capable of learning and following routes in complex natural environments using relatively constrained sensory and neural systems. Such capabilities are particularly relevant to applications such as agricultural robotics, where visual navigation through dense vegetation remains a challenging task. In this scenario, a route is likely to have high s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 110 publications
0
2
0
Order By: Relevance
“…Some earlier MB-inspired models suggested that such connectivity could allow dynamic recurrent patterns to emerge in KC firing (Payne et al 2010;Arena et al 2013), followed by adaptive linear readout by the MBONs, resembling a reservoir network (Schrauwen et al 2007). A more recent model has explored if adaptive connections between KCs could contribute to learning sequences of sensory patterns in a visual navigation context (Zhu et al 2023).…”
Section: What Lies Beyond?mentioning
confidence: 99%
“…Some earlier MB-inspired models suggested that such connectivity could allow dynamic recurrent patterns to emerge in KC firing (Payne et al 2010;Arena et al 2013), followed by adaptive linear readout by the MBONs, resembling a reservoir network (Schrauwen et al 2007). A more recent model has explored if adaptive connections between KCs could contribute to learning sequences of sensory patterns in a visual navigation context (Zhu et al 2023).…”
Section: What Lies Beyond?mentioning
confidence: 99%
“…In addition to addressing two distinct grand challenges [25,26], BRAID sought to advance the application of a new class of brain-inspired engineering learning system based on novel or existing neuroscience theories [27][28][29][30][31] in the domain of autonomous systems, including neuromorphic sensors [32][33][34], brain-inspired robots [35][36][37], metacontrollers for multi-agent robots [38][39][40], neuromorphic medical technologies [41,42], and other applications with global economic and health benefits. BRAID especially focused on improving performance metrics beyond energy-and data-efficient learning algorithms [20,43] and learning hardware, including the development of neuromorphic systems [10,[44][45][46], the designs of which were based on insights from recent neuroscience advances [27,31,[47][48][49][50][51][52].…”
Section: Introductionmentioning
confidence: 99%